Organization of Continuing Professional Training of Employees in the System of Forensic Science Organizations of the Russian Ministry of Justice - M. V. Toropova (Теория и практика судебной экспертизы)
The paper outlines the organizational framework of forensic expert training in the system of forensic science organizations of the Russian Ministry of Justice, developed and implemented by the Educational Methodology Department of the RFCFS of the Russian Ministry of Justice. Problematic organizational and methodological issues of the training process are highlighted, and possible solutions are examined.